Establishing a Research Agenda for Suicide Prevention Among Veterans Experiencing Homelessness - Robinson, Maurand; Holliday, Ryan; Monteith, Lindsey L.; Blosnich, John R.; Elbogen, Eric B.; Gelberg, Lillian; Hooshyar, Dina; Liu, Shawn; McInnes, D. Keith; Montgomery, Ann Elizabeth; Tsai, Jack; Grassmeyer, Riley; et al. (Frontiers in Psychology, 2022)
Suicide among Veterans experiencing or at risk for homelessness remains a significant public health concern. Conducting research to understand and meet the needs of this at-risk population remains challenging due to myriad factors (e.g., clinical complexity including multimorbidity, difficulty monitoring risk across systems). To address this challenge, the United States Department of Veterans Affairs (VA) convened the Health Services Research and Development (HSR&D) Suicide Prevention in Veterans Experiencing Homelessness: Research and Practice Development meeting, bringing together subject-matter experts in the fields of homelessness and suicide prevention, both from within and outside of VA. During the meeting, attendees identified ten potential research priorities at the intersection of suicide prevention and homelessness. After the meeting, Delphi methodology was used to achieve consensus on the relative importance of the identified research domains. Through this iterative Delphi process, agreement was reached regarding the need to increase understanding of barriers and facilitators to suicide risk assessment and emergency intervention for Veterans experiencing homelessness by examining the perspectives of both Veterans and healthcare providers. Elucidating the complex relationships between risk periods, subgroups, suicide means, and drivers of suicide among Veterans experiencing homelessness was also considered a top priority. This article documents the Delphi process and provides a research agenda for researchers, funding agencies, and policy makers to prioritize the most relevant and potentially impactful research domains aimed at preventing suicide among Veterans experiencing or at risk for homelessness.